PERANCANGAN SISTEM INFORMASI AKUNTANSI YANG DILENGKAPI DENGAN PERHITUNGAN PAJAK PERTAMBAHAN NILAI - Rachmasari, Fitria Melati; Susilowati, Meme; Setiawan, Rudy (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2023)
The internet has become an essential part of daily life, supporting various activities such as studying and exchanging news. Internet installation service providers, such as PT Cyber Access Indonesia, play a crucial role in meeting these needs. However, not all internet service providers currently utilize information systems that allow for easy, fast, and accurate data storage and retrieval, as seen in PT Cyber Access Indonesia. This study aims to address existing issues within the company by developing a new information system: an accounting information system that includes value-added tax calculations and customer data processing. The research employs the Three Major Phases method, which consists of analysis, design, and implementation. The design technique used is UML (Unified Modelling Language), and the system is developed using the PHP programming language and MySQL database. The outcome of this study is the implementation of an accounting information system that facilitates transaction recording and financial statement preparation.